(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
There was made the systematic analysis of the flora of the regional landscape park «Gadyachsky». Its flora is represented by 923 species of vascular plants. There are 437 genera, 111 families and 5 departments. The high level of floristic richness of the park is determined by multi-territory differentiation and ecotonic effect. There was given numeral characteristics of the specific composition of the main taxonomic items, principal proportions of the flora. (Liliopsida/Magnoliopsida; genera/species; families/ genera/ species), number of species of main families and genera spectra. In the stectrum of the principal families dominate Asteraceae (117 species; 12,6 %), Poaceae (63; 6.8), Brassicaceae (52; 5,6), Fabaceae (52; 5,6), Lamiaceae (47; 5,1), Caryophyllaceae (46; 5,0), Rosaceae (45; 4,8), Ranunculaceae (36; 3,9), Apiaceae (34; 3,7), Scrophulariaceae (26; 2,8). The most polymorphous genera are Carex (20 species; 2,2%), Chenopodium (14; 1,6), Veronica (13; 1,4), Ranunculus (13; 1,4), Galium (12; 1,3), Dianthus (10; 1,1), Salix (10; 1,1), Potentilla (10; 1,1), Vicia (10; 1,1), Trifolium (9; 1,0). The flora of the park has closely-related character between Mediterranean-Eurasian and Boreal floras.